3 - Can we speak of African agency?: APRM and Africa’s agenda 2063 - Roseline M. Achieng' (African Sociological Review, 2015)
In marking the golden jubilee of the Organisation of African Unity (OAU) now the African Union (AU), the African Union Commission announced its intended objective of having a document that would be a vision for Africa’s integration, peace and development in the coming 50 years. Currently, a draft AU Agenda 2063 is in circulation with an invitation to key stakeholders to input into its objectives of outlining a broad framework of transformation of the continent. This paper is borne with this in mind. The main argument that is advanced is that the African Peer Review Mechanism (APRM), adopted as a programme of the African Union in March 2003, demonstrates African agency in tackling political, economic, corporate and social economic governance deficiencies. Through exploring ‘best practices’ in certain select countries the main thrust of the paper will be to showcase this African agency. It is argued that the AU’s Agenda 2063 would certainly hold greater legitimacy in strategically positioning itself in global geopolitics by demonstrating that existing African initiated institutions aimed at the transformation of society, for example the APRM, have indeed provided ‘African solutions to Africa’s problems’. The processes that have brought about progress thus far should not only be reflected in the AU’s Agenda 2063, these should further be supported both regionally and internationally as Africa continues to pursue its vision of an African Renaissance and show casing African agency in regional and global transformations.